Studying the Pharmacokinetics of Interleukin-1RA Mutants - Iqra Khuzaima; Kanwal Iftikhar; Uroosa Tabarruk; Haleema Sadia; Khadija Shami (BioScientific Review, 2019)
The two antagonists for interleukin-1 (IL-1) system are IL-1α, and IL-1β. IL-1 receptor antagonist (IL-1RA) is another naturally occurring non-competitive antagonist. All three antagonists are bound to two receptors that are IL-R1 and IL-1R2. IL-1 is a well-studied pro-inflammatory cytokine that is involved in chronic inflammatory diseases such as rheumatoid arthritis, Parkinson's disease, Alzheimer's, stroke, and epilepsy. The existing literature suggests that interleukin-1 (IL-1) biological responses are impeded by interleukin-1 receptor antagonist (IL-1RA) belonging to interleukin-1 (IL-1) family and a natural IL-1 inhibitor acting as ‘receptor antagonist’. Various studies based on different clinical and experimental models suggest that IL-antagonism has been reported beneficial in neuropathalogical conditions, whereas, pro-inflammatory actions of IL-1 receptor antagonist (IL-1RA) seem detrimental. This study was performed to ameliorate the stability of IL-1RA mutants generated by mutagenesis at specific sites like R6K7-AA, R93K94-AA and K97R98-AA. Using pTIG-Trx expression system, mutants were expressed in E. coli BL21 (DE3) accompanied with the induction of (isopropyl β-D-1-thiogalactopyranoside) IPTG. Later on, the purification of recombinant proteins was brought about using SephadexG75 gel filtration chromatography and Ni+2 chelate chromatography. The bioactivity assay result exhibited IL-IRA activity as high as mutants’ activity. The characterization of pharmacokinetic profile of IL-1RA apace with its mutants presents the half-life of third mutants 2.11 times longer than that of wt IL-1RA. This experimental study will lead to novel approaches, experiences and baseline data, thus providing basis for further research to outdo and elevate the metabolic stability of IL-1RA.